2021
DOI: 10.1111/ecog.05759
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic niche conservatism and variations in species diversity–climate relationships

Abstract: Although contemporary climate has been identified as one of the major determinants of large-scale species diversity patterns, its effect on species diversity greatly varies among clades. Understanding the drivers of the variation in species diversity-climate relationships (DCRs) across clades, which is critical for developing general mechanisms underlying the effects of climate on species diversity patterns, remains a current challenge. Using newly compiled distribution data of 914 Rosaceae species in China an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 67 publications
(88 reference statements)
2
10
0
Order By: Relevance
“…These results suggest that niche conservatism among the three evolutionary factors that we evaluated was the dominant factor of the variations in species richness–climate relationships. This finding is consistent with recent studies on the variations in species richness–climate relationships for eastern Asian woody plants (Su et al, 2020) and Chinese Rosaceae (Wang et al, 2021). Our results further revealed that the discrepancy between contemporary and ancestral climatic niches dominated the variation in species richness–climate relationships across different families, which reveals the specific impact of niche conservatism on species richness–climate relationships.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that niche conservatism among the three evolutionary factors that we evaluated was the dominant factor of the variations in species richness–climate relationships. This finding is consistent with recent studies on the variations in species richness–climate relationships for eastern Asian woody plants (Su et al, 2020) and Chinese Rosaceae (Wang et al, 2021). Our results further revealed that the discrepancy between contemporary and ancestral climatic niches dominated the variation in species richness–climate relationships across different families, which reveals the specific impact of niche conservatism on species richness–climate relationships.…”
Section: Discussionsupporting
confidence: 93%
“…This finding suggests that due to niche conservatism, climate has a weak influence on species richness in areas or clades with climates similar to the ancestral conditions under which clades diversified, but the effect of climate is strengthened when one gets away from the ancestral climate of clades. Compared to previous research (Gouveia et al, 2013; Su et al, 2020; Wang et al, 2021), our study further explored how the effect of climate on species richness is moderated by niche conservatism, which extends the original niche conservatism hypothesis and provides a new perspective for understanding the response of species richness to climate change.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Phylogenetic niche conservatism may explain various patterns in closely-related species such as divergence of foraging niches to avoid competition (Lovette and Hochachka, 2006), maintaining ancestral adaptation to certain environmental conditions (e.g., Morinière et al, 2016), and similarity in diversity-climate relationships (e.g., Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%